Implementation Of Plant Cultivation System Policy Sagu in Improving Community Food in Tambat Village - Petrus Watonem; Syahruddin; Syahrabudin Husein Enala (Papsel Journal of Humanities and Policy, 2024)
This study a of the ims to determine how the implementation of the sago cultivation policy, as well as to determine what factors influence the implementation of the sago cultivation policy in Tambat Village, Tanah Miring District, Merauke Regency, which are still not effective, as for the factors that influence the implementation of the Cultivation policy. Sago plants in Tambat village are seen from the cultivation of sago plants. Busides that, there is also the theory used by researchers, namely: George Edward III’s theory is that the factors that influence the implementation of the sago cultivation policy in Tambat Village, Tanah Miring District, Merauke Regency are the first communication factors, rarely done, resource factors, which are not supportive, disposition factors/ attitudes that are not resp